Analisis Kesulitan Siswa Dalam Menyelesaikan Soal Pada Materi Barisan dan Deret Aritmatika dengan Menggunakan Model Pembelajaranm Make A MATCH - Khoirunnisa; Nova Christina Dewi; Puspa Riani Nasution (JURNAL CERMATIKA, 2025)
This research aims to determine: (1) students' difficulties in understanding the concept of arithmetic sequences and series, (2) students' difficulties in applying the principles of arithmetic sequences and series in solving problems, and (3) students' difficulties in finding information contained in sequences and arithmetic series questions. arithmetic series using the Make a Match learning model in class XI IPS 1 SMA NEGRI 8 Padangsidimpuan. The research carried out was qualitative research using qualitative descriptive methods. The subjects in this research were students of class XI IPS 1 SMA NEGRI 8 PADANGSIDIMPUAN. Data collection techniques by means of interviews with tests.The results of the research showed that the 4 students who were interviewed and completed the test questions found that the four students had different difficulties in solving sequence and series story questions. In understanding concepts, students who have difficulty will find it difficult to understand the concept of arithmetic sequences and series and will not be able to apply it to story problems for arithmetic sequences and series. When finding the information contained in the problem, students who experience difficulty will find it difficult to find the information and convert the mathematical information into the form of a mathematical model so they will experience difficulty in determining principles or formulas if the information contained in the story is not known beforehand.